Peran pesantren dalam menjaga etika Nusantara - Moh. Affan; Firdausi, Himami; Babun Suharto (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2025)
The erosion of moral values and local wisdom in the era of pluralism and rapid modernization has raised concerns about the sustainability of ethical foundations in Indonesian society. This study aims to examine how Islamic boarding schools (pesantren) preserve and reinforce Nusantara ethics amid these contemporary challenges. Employing a qualitative approach with a library research design, data were collected from books, peer-reviewed journal articles, and relevant research reports. The findings indicate that pesantren maintain ethical continuity through the integration of Nusantara ethics into their curriculum, adaptive responses toward modernity, and the exemplary moral leadership of kyai supported by a disciplined santri culture. The discussion highlights enabling factors such as charismatic leadership, adab-centered educational practices, community involvement, and technological literacy, while also identifying challenges that include global cultural pressures, resource limitations, and shifting digital morals. In conclusion, pesantren continue to function as ethical and cultural strongholds that safeguard Indonesia’s moral identity in the modern era.